Combined use of biochar with 15Nitrogen labelled urea increases rice yield, N use efficiency and fertilizer N recovery under water-saving irrigation - Haque, Ahmad Numery Ashfaqul; Uddin, Md. Kamal; Sulaiman, Muhammad Firdaus; Mohd Amin, Adibah; Hossain, Mahmud; M. Solaiman, Zakaria; Abd Aziz, Azharuddin; Mosharrof, Mehnaz (MDPI, 2022)
Biochar is a potential carbon-rich soil amendment that improves the physicochemical properties of soil, besides acting as a controlled release fertilizer. An experiment was conducted to investigate the effect of biochars on rice yield, fertilizer use efficiency and recovery under water-saving irrigation by 15N isotopic tracer study. Two types of irrigation as alternate wetting and drying (AWD) and continuous flooding (CF), and four types of biochar treatments such as rice husk biochar (RHB) with 15N urea, oil palm empty fruit bunch biochar (EFBB) with 15N urea, 15N urea alone and control, were applied to assess their impact on rice. About 4% reduced grain yield with 18% improved water productivity was achieved by the AWD regime over the CF, whereas RHB and EFBB significantly increased rice yield compared to unamended soil. RHB and EFBB enhanced the water productivity up to 25.3%. The fertilizer N uptake and recovery were boosted by RHB and EFBB up to 18.8% and 24.5%, respectively. RHB and EFBB accelerated the agronomic use efficiency and partial factor productivity of N (up to 21% and 8%, respectively). RHB and EFBB profoundly enhanced the pH, the total C and N and the available N (NH4+ and NO3−) of the post-harvest soil. This study suggests that adding RHB and EFBB with urea improves fertilizer N utilization and soil N retention, and their combination with AWD could enhance rice yield with better water productivity due to their porous structure and controlled N release capacity.